2013
DOI: 10.1177/0956797613497022
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Reversals in Risky Decision Making

Abstract: Intelligence agents make risky decisions routinely, with serious consequences for national security. Although common sense and most theories imply that experienced intelligence professionals should be less prone to irrational inconsistencies than college students, we show the opposite. Moreover, the growth of experience-based intuition predicts this developmental reversal. We presented intelligence agents, college students, and postcollege adults with 30 risky-choice problems in gain and loss frames and then c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 41 publications
6
126
0
Order By: Relevance
“…Indeed, studies have found that explanations regarding antibiotics’ lack of effectiveness against viral infections were not well understood (4), and there is some reason to believe that this would be especially true for the least educated patients – in our sample, most patients had, at most, a high school education. When interpreted in light of other FTT research on risk-taking (16), this study’s results suggest that conventional strategies aimed at educating patients regarding potential side effects and other downside risks must communicate that such risks are both qualitatively worse than the status quo of being sick (e.g., 17-24), and that there is virtually no upside potential to inappropriate antibiotic use. Communications that explicitly focus on communicating that antibiotics are harmful – rather than providing verbatim data – may shift patient preferences (4, 25).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Indeed, studies have found that explanations regarding antibiotics’ lack of effectiveness against viral infections were not well understood (4), and there is some reason to believe that this would be especially true for the least educated patients – in our sample, most patients had, at most, a high school education. When interpreted in light of other FTT research on risk-taking (16), this study’s results suggest that conventional strategies aimed at educating patients regarding potential side effects and other downside risks must communicate that such risks are both qualitatively worse than the status quo of being sick (e.g., 17-24), and that there is virtually no upside potential to inappropriate antibiotic use. Communications that explicitly focus on communicating that antibiotics are harmful – rather than providing verbatim data – may shift patient preferences (4, 25).…”
Section: Discussionmentioning
confidence: 77%
“…16). Patients who make such categorical distinctions should seek antibiotic therapy if there is a non-negligible possibility that their symptoms are caused by a bacterial pathogen and could improve with antibiotics.…”
Section: Hypothesesmentioning
confidence: 99%
“…Indeed, Reyna, Chick, Corbin, and Hsia (2014) showed that intelligence analysts were more susceptible to risky-choice framing effects than either college students or postcollegiate adults, perhaps because they had developed bad habits in an "unfriendly" environment. Although experts may, on average, be poor at exercising good judgment in complex domains like geopolitical forecasting, others suspect that there are systematic individual differences-and that some forecasters will consistently outperform others (Bueno de Mesquita, 2009;Tetlock, 2005).…”
Section: Consistency In Forecasting Skillsmentioning
confidence: 99%
“…44 Indeed, “the preference to operate on the crudest gist, the fuzzy-processing preference, increases with experience or expertise.” 25,46-49 When people make decisions, it is often more helpful to rely on these fuzzy gist representations 25,49-55 provided that they accurately capture decision-relevant features. Research indicates that gist representations are better retained, less vulnerable to extraneous interference, and easier to manipulate compared with verbatim representations, all of which reduces errors.…”
Section: Fuzzy-trace Theorymentioning
confidence: 99%